Etiology and outcome of mono-articular arthritis: a follow up study - Sonawale, Archana; Sabnis, Nilakshi Harshad; Karale, Maroti (International Journal of Advances in Medicine, 2018)
Background: Monoarthritis is a common rheumatological complaint. Inspite of investigations, many cases remain undiagnosed. Prompt investigation and treatment is important in acute arthritis especially septic arthritis else joint destruction, permanent disability or even death can result. This study was conducted to etiologically categorise patients as inflammatory, non-inflammatory and infective arthritis and to study the outcome. Methods: This observational prospective study conducted at a tertiary care hospital in Mumbai enrolled 40 patients above the age of 12 yrs presenting with first episode of mono-articular arthritis. They were treated with standard treatment guidelines and followed up every 3 monthly for one year. Outcome was assessed using ESR, CRP values and Health Assessment Questionnaire. Results: Mean age at diagnosis was 38 years with a male to female ratio of 1.4:1. Acute and chronic mono-articular arthritis cases were 16.2% and 83.7% respectively. Knee joint was most commonly involved (38%). Etiologically inflammatory, infectious and non-inflammatory cases were 59.5%, 29.7% and 10.8% respectively. In 21% cases etiology was tuberculosis. 27 % evolved into oligoarthritis over one year. The serial ESR, CRP values and Stanford Health Assessment Questionarre scores decreased significantly across all etiological groups with treatment. Conclusions: Knee is the most commonly affected joint in mono-articular arthritis. Tuberculosis is the most common etiology. Irrespective of the etiology, if patients are treated according to standard guidelines promptly mono-articular arthritis has a good response to therapy as assessed by the health assessment questionnaire (HAQ) and serial measurements of proinflammatory markers like ESR, CRP.